Sulfur Dioxide (SO2) Detection Using Composite of Nickel Benzene Carboxylic (Ni3BTC2) and OH-Functionalized Single Walled Carbon Nanotubes (OH-SWNTs) - Ingle, Nikesh; Mane, Savita; Sayyad, Pasha; Bodkhe, Gajanan; AL-Gahouari, Theeazen; Mahadik, Manasi; Shirsat, Sumedh; Shirsat, Mahendra D. (Frontiers in Materials, 2020)
In the present investigation, a composite of “nickel benzene carboxylic (Ni3BTC2)” and “OH-functionalized single walled carbon nanotubes (OH-SWNTs)” was synthesized using the solvothermal method. The synthesized Ni3BTC2/OH-SWNTs were drop casted on gold micro electrode tip on Si/SiO2 substrate. The synthesized composite materials were characterized by X-ray diffraction (XRD) for structural analysis, electrical analysis using current-voltage (I/V) characteristics, Field emission scanning electron microscopy (FESEM) for surface morphology, Field effect transistor (FET) by using transfer and output characteristics, and spectroscopic analysis using Fourier-transform infrared spectroscopy (FTIR). This composite was used for the detection of SO2. The proper incorporated OH-SWNTs in Ni3BTC2 MOF exhibits increased conductivity and sensing performance (better response and recovery time and repeatability). This work reveals that the composite of Ni3BTC2/OH-SWNTs can be used for reversible sensing of SO2 gas in ChemFET modality at room temperature.